2007
DOI: 10.1021/ja069065d
|View full text |Cite
|
Sign up to set email alerts
|

A New Multicomponent Reaction Catalyzed by a [Lewis Acid]+[Co(CO)4]- Catalyst:  Stereospecific Synthesis of 1,3-Oxazinane-2,4-diones from Epoxides, Isocyanates, and CO

Abstract: The use of mechanistic information to develop a new, catalytic multicomponent reaction is described. The complex [(salph)Al(THF)2]+[Co(CO)4]- (1, salph = N,N'-o-phenylenebis(3,5-di-tert-butylsalicylideneimine), THF = tetrahydrofuran), which is known to carbonylate epoxides, aziridines, and beta-lactones, was used to catalyze the synthesis of 1,3-oxazinane-2,4-diones from epoxides, isocyanates, and CO. Under optimized conditions, the reaction was both selective and high-yielding. 1,3-Oxazinane-2,4-diones were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“… Some examples of MCRs such as Strecker synthesis, Hantzsch reaction, Biginelli reaction, Mannich reaction, and Ugi reaction are well documented. In comparison, electrophilic MCRs have been less reported . A likely reason might be due to the common incompatibility of electrophiles with the other components.…”
Section: Nbs‐initiated Multicomponent Reactions (Mcrs)mentioning
confidence: 98%
“… Some examples of MCRs such as Strecker synthesis, Hantzsch reaction, Biginelli reaction, Mannich reaction, and Ugi reaction are well documented. In comparison, electrophilic MCRs have been less reported . A likely reason might be due to the common incompatibility of electrophiles with the other components.…”
Section: Nbs‐initiated Multicomponent Reactions (Mcrs)mentioning
confidence: 98%
“…The more challenging 1,2-disubstituted oxirane substrates required pressurized CO conditions, but still far lower than when aluminum was employed as the Lewis acid. In 2013, Jurczak reported that the Coates catalyst can be generated in situ from the corresponding chloride salt by reacting in the presence of Co 2 (CO) 8. With this method, handling oxygen sensitive Na[Co(CO) 4 ] is avoided, and the reaction also proceeds with MTBE as solvent [3].…”
Section: Carbonylation and Co 2 Fixation Of Oxirane Substratesmentioning
confidence: 99%
“…Professor Coates next reported that the intermediate aluminum alkoxide complex could be intercepted with an electrophile prior to the terminating cyclization step (Scheme 3) [4]. By using highly reactive isocyanates as electrophiles, Scheme 1 Carbonylation enabled by an aluminum Lewis acid catalyst 1,3-oxazinane-2,4-diones can be accessed in a single step from oxiranes.…”
Section: Carbonylation and Co 2 Fixation Of Oxirane Substratesmentioning
confidence: 99%
See 1 more Smart Citation
“…[40] Other 1,3-oxazinanones are known as well. [41,42,43] Biological testing: The described analogues as well as the diyne 53 were tested for cytotoxicity against the L929 cell line and the inhibitory efficacy on F-ATPase in mitochondrial preparations of bovine heart. The obtained IC 50 values in the cell-culture assay as well as the percentage of F-ATPase inhibition of the compounds at a concentration of 0.1 and 1.0 mm, respectively, are listed in Table 2.…”
Section: Introductionmentioning
confidence: 99%